Efficacy of Family Meeting for severe sepsis in Medical ICU, Maharaj Nakorn Chiang Mai Hospital - Wongpalee, Tula; Kantha, Monticha; Inchai, Juthamas (Biomedical Sciences and Clinical Medicine, 2017)
Objective To assess family satisfaction between normal information and family meeting for severe sepsis and completeness of information at 24, 72 hours and discharge. Methods A pre-post intervention study was compared among normal information and family meeting for severe sepsis in Medical ICU during June 2014 to may 2016. Results Eighty-eight patient’s families were compared between pre and post family meeting information for severe sepsis, the results revealed a post intervention group had statistically signi fi cant higher mean score of patient or family’s satisfaction within 24, 72 hours and discharge period in case of survived and dead (p<0.05). The information process was also completed in every stage. Conclusion The family meeting information for severe sepsis has made patient or family high satisfaction and improved quality of nursing care.